Online counselling: Application of cognitive behaviour therapy and music counselling to reduce math anxiety - Purnomo, Andreas Wisnu Adi; Loekmono, J.T Lobby (Universitas Islam Negeri Raden Intan Lampung, 2021)
Math anxiety is one of the causes of the low achievement of students in mathematics lessons. Guidance and counselling teachers need strategies for students who experience math anxiety. This study aims to determine an effective counselling approach to reduce students' math anxiety. This type of research is a single subject experiment with multiple baseline designs. The sampling technique used was purposive sampling. The research subjects were 2 individuals. The data analysis technique consisted of data analysis using Mann Whitney and qualitative time triangulation techniques. Based on the research results, cognitive behaviour therapy and music counselling can reduce students' math anxiety. Several techniques in cognitive behaviour therapy affect many aspects such as feelings, thoughts, physical sensations, and actions. In music counselling, the lyrics and lyrics of the songs shift the focus of the individual who was originally fixated on the fear of facing math problems to become calmer during math lessons